Glucosamine-containing supplement improves locomotor functions in subjects with knee pain a randomized, double-blind, placebo-controlled study - Kanzaki, Noriyuki; Ono, Yoshiko; Shibata, Hiroshi; Moritani, Toshio (Clinical interventions in aging, 2015)
The aim of this study was to investigate the ability of a glucosamine-containing supplement to improve locomotor functions in subjects with knee pain. A randomized, double-blind, placebo-controlled, parallel-group comparative study was conducted for 16 weeks in 100 Japanese subjects (age, 51.8±0.8 years) with knee pain. Subjects were randomly assigned to one of the two supplements containing 1) 1,200 mg of glucosamine hydrochloride, 60 mg of chondroitin sulfate, 45 mg of type II collagen peptides, 90 mg of quercetin glycosides, 10 mg of imidazole peptides, and 5 μg of vitamin D per day (GCQID group, n=50) or 2) a placebo (placebo group, n=50). Japanese Knee Osteoarthritis Measure, visual analog scale score, normal walking speed, and knee-extensor strength were measured to evaluate the effects of the supplement on knee-joint functions and locomotor functions. In subjects eligible for efficacy assessment, there was no significant group × time interaction, and there were improvements in knee-joint functions and locomotor functions in both groups, but there was no significant difference between the groups. In subjects with mild-to-severe knee pain at baseline, knee-extensor strength at week 8 (104.6±5.0% body weight vs 92.3±5.5% body weight, P=0.030) and the change in normal walking speed at week 16 (0.11±0.03 m/s vs 0.05±0.02 m/s, P=0.038) were significantly greater in the GCQID group than in the placebo group. Further subgroup analysis based on Kellgren-Lawrence (K-L) grade showed that normal walking speed at week 16 (1.36±0.05 m/s vs 1.21±0.02 m/s, P<0.05) was significantly greater in the GCQID group than in the placebo group in subjects with K-L grade I. No adverse effect of treatment was identified in the safety assessment. In subjects with knee pain, GCQID supplementation was effective for relieving knee pain and improving locomotor functions.